Risk management plan (RMP) : implementation and challenges towards sustainability and green concept for public projects in Terengganu / Yuhainis Abdul Talib, Siti Nirwana Mat Usof and Kharizam Ismail - Yuhainis, Abdul Talib; Siti Nirwana, Mat Usof; Kharizam, Ismail (2015)
Risk management become be the most significant and integral part of project management. The construction project may fail or succeed, depending on the adopted risk management approach. As risk management is predicting the unpredictable, it is one of the most vital management tools to cope with project risks and uncertainties. In Jabatan Kerja Raya (JKR), risk management is being implemented as part of the project management plan. Despite going through the process, some JKR‟s project still have problem in the project delivery. Due to this scenario, the objective of this study is to identify the level awareness in implementing the risk management to public authority (JKR). Futhermore, it will also aim to identify and rank the challenges faced by JKR in managing risk management in public projects. Questionnaire survey was carried out in order to obtain a better view of result. Although JKR‟s organization is provided with standard guideline and most of them aware about it, but it will still face with the construction risks as there is no supervision or weakness in monitoring about implementation of risk management in construction project. Therefore, sufficient knowledge, practice and systematic risk management is essential to reduce the complexity and uncertainties in construction project and finally can promote sustainability toward green concept in finishing project in due time.